2002
DOI: 10.1080/07399330290112380
|View full text |Cite
|
Sign up to set email alerts
|

Stroll Your Way to Well-Being: A Survey of the Perceived Benefits, Barriers, Community Support, and Stigma Associated With Pram Walking Groups Designed for New Mothers, Sydney, Australia

Abstract: In our survey of 500 mothers with children 0-5 years involving telephone interviews (n = 450) and focus groups (n = 50), we showed that 87% of mothers telephone surveyed used a pram for incidental activities, whilst 47% used the pram specifically for exercise. Factors preventing mothers exercising more included poor weather, lack of time, and poor quality paths. Ninety-two percent of mothers believed that pram walking would increase mental well-being, and 87% felt that it would help to reduce postnatal depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 9 publications
1
58
1
Order By: Relevance
“…Albright, Maddock, and Nigg (2005) reported that only 35% of women who were active before childbirth were active after childbirth. This is despite Currie and Develin's (2002) finding that 69% of women in the postnatal period indicated that they would like to exercise more. Clearly, further research examining predictors of physical activity and inactivity in this specific and important population is well justified.…”
contrasting
confidence: 70%
“…Albright, Maddock, and Nigg (2005) reported that only 35% of women who were active before childbirth were active after childbirth. This is despite Currie and Develin's (2002) finding that 69% of women in the postnatal period indicated that they would like to exercise more. Clearly, further research examining predictors of physical activity and inactivity in this specific and important population is well justified.…”
contrasting
confidence: 70%
“…In particular, young and midlife women generally report positive attitudes towards physical activity (Currie & Develin, 2002), but population surveys show that this population has one of the lowest levels of actual physical activity (Armstrong, Bauman, & Davis, 2000;Currie & Develin, 2002). In light of the research of Lowe et al (2002), it is conceivable that only women's instrumental attitudes to physical activity are positive.…”
Section: Implications For Interventionsmentioning
confidence: 99%
“…It is in these middle adulthood years that women can be expected to be having and raising children, starting and developing careers, and managing their immediate and extended families. A common thread in much of the research investigating the barriers to physical activity in young and midlife women, particularly women with children under 16, is that they do not have the time to engage in regular physical activity (Anderson, 2003;Brown et al, 2001;Currie & Develin, 2002;Eyler et al, 2002;Johnson et al, 1990;Miller, Trost, & Brown, 2002 perceived barrier to physical activity that was the same for black and white, young and old, women, was lack of time due to work or school, household, and children.…”
Section: Implications For Interventionsmentioning
confidence: 99%
“…The link between weather and physical activity is well established. Increased bright sunshine time could increase daily walking [38] and outdoor activities [39]; higher rainfall and weed speed is likely to be associated with lower physical activity level [40][41][42][43]; temperature could have different impacts on physical activity across areas and seasons [44]. For the season during which we conducted our study in Hong Kong, we found that bright sunshine time was significantly associated with an increase in players' walking and running distance, while total rainfall, mean air temperature, and mean wind speed were negatively correlated with the distance.…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 99%